Preservation of Denonvilliers' fascia for nerve‐sparing laparoscopic total mesorectal excision: A neuro‐histological study. Issue 3 (5th February 2019) - Liu, Jianpei; Huang, Pinjie; Liang, Qiong; Yang, Xiaofeng; Zheng, Zongheng; Wei, Hongbo
Abstract : Urogenital complications due to pelvic autonomic nerve damage frequently occur following rectal surgery. We investigated whether total mesorectal excision (TME) with preservation of the Denonvilliers' fascia (DVF) can effectively prevent the removal of pelvic autonomic nerves through microscopy. Twenty consecutive male patients with mid‐low rectal cancer who received TME with preservation or resection of the Denonvilliers' fascia (P and R groups, respectively) were included. Serial transverse sections from surgical specimens were studied histologically. Nerve fibers at the surfaces of the mesorectum were counted. Clinical correlation between the amount of nerve fibers removed and post‐operative sexual function was analyzed. Nerve fibers closely localized to the DVF in the R group displaying rich erectile activity (positive anti‐nNOS immunostaining). At the anterior surface of the mesorectum, the mean numbers of nNOS‐positive nerve fibers per specimen in the P group were significantly lower than the R group (3.0 ± 1.8 vs. 5.0 ± 2.3, P  < 0.05). Compared to the R group, patients in the P group had higher IIEF scores and better erectile function at 3 and 6 months post‐operatively. The DVF is a key risk zone for pelvic denervation during laparoscopic TME. Preservation of the DVF can prevent the removal of autonomic nerves and protect post‐operative erectile function. Clin. Anat. 32:439–445, 2019. © 2019 Wiley Periodicals, Inc.